Uztvertās vecāku pārraudzības un uztvertās iesaistīšanās bērna izglītībā saistībā ar alkohola lietošanas biežumu pusaudžiem. - Zotova, Darja (Latvijas Universitāte, 2014)
Pētījuma mērķis bija noskaidrot, kādas saistības pastāv starp uztverto vecāku pārraudzību, iesaistīšanos bērna izglītībā un pusaudža alkohola lietošanas biežumu. Tika izvirzīti divi pētījuma jautājumi – kāda saistība pastāv starp uztverto vecāku pārraudzību un alkohola lietošanas biežumu un kāda saistība pastāv starp vecāku iesaistīšanos bērnu izglītībā un alkohola lietošanas biežumu? Darba teorētiskajā daļā ir raksturota vecāku pārraudzība un iesaistīšanās bērnu dzīvē, kā arī raksturota pusaudžu alkohola lietošana un lietošanas iemesli, apskatīti mūsdienu pētījumi un to rezultāti. Pētījumā piedalījās 50 respondenti vecumā no 13 līdz 15 gadiem (M=14,3; SD=8,72), no tiem 58% meitenes un 42% zēni. Pētījuma dalībnieki aizpildīja „Vecāku iesaistīšanās bērnu mācīšanās procesā aptauju” (Parents' involvement in children's learning scale, Chao, 2000; Kerr & Stattin, 2000; Kohl, Lengua, McMahon, & the Conduct Problems Prevention Research group, 2000; Stattin & Kerr, 2000), „Vecāku pārraudzības aptaujas” (Parental monitoring scale; Kerr & Stattin, 2000) un „Alkohola lietošanas biežuma aptaujas” (Drug and Alcohol Use - Youth risk behavior survey, CDC, 1993). Pētījuma rezultāti parāda, ka pastāv statistiski nozīmīga negatīva saistība starp vecāku iesaistīšanos bērnu mācīšanās procesā un bērna alkohola lietošanas biežumu (r = -0,24, p < 0,01); pastāv statistiski nozīmīga negatīva korelācija starp uztverto vecāku pārraudzību un bērna alkohola lietošanas biežumu (r = -0,18, p < 0,05). Rezultāti parāda ka, jo lielāka ir vecāku iesaistīšana bērna izglītībā un uztvertas vecāku pārraudzība, tad pusaudzis mazāk lieto alkoholu. Atslēgvārdi: vecāku pārraudzība, vecāku iesaistīšanās, alkohola lietošanas biežums, pusaudži.

The aim of research was to clarify the correlations between perceived parental monitoring and involvement in education and the frequency of alcohol use. Two research questions were put forward- what is the relationship between perceived parental monitoring and frequency of alcohol use; the relationship between parental involvement in children's education and frequency of alcohol use. In the theoretical part of the work the meaning of the parental monitoring and involvement in children's lives was described, as well as the causes of teenagers’ alcohol use, the contemporary studies and their results were explored. The practical part describes the study participants, tools and procedures, as well as the presentation of research results and their discussion. The study included 50 respondents aged 13-15 years (M=14,3; SD=8,72), 58% of which were girls and 42% boys. The study participants completed the following surveys: “Parental involvement in children's education” (Parents' involvement in children's learning scale, Chao, 2000; Kerr & Stattin, 2000; Kohl, Lengua, McMahon, & the Conduct Problems Prevention Research group, 2000; Stattin & Kerr, 2000), “Parental monitoring“ (Parental monitoring scale; Kerr & Stattin, 2000) and ”The frequency of alcohol use” (Drug and Alcohol Use - Youth risk behavior survey, CDC, 1993). From the results obtained within the framework of Bachelor work study it can be concluded that: there is a statistically significant negative correlation between parental involvement in children's education and the frequency of teenagers’ alcohol use (r = -0,24, p < 0,01); there is a statistically significant negative correlation between parental monitoring and the frequency of teenagers’ alcohol use (r = -0,18, p < 0,05). The results show that if parental involvement in children's education and parental monitoring is higher, then the teenager frequency of alcohol use is lower. Keywords: parental monitoring, parental involvement, use of alcohol.
Parental monitoring and involvement in children's education in the framework of the teenagers' alcohol use frequency.
Keywords: Psiholoģija